Scalable detection of cellular protein-small molecule interactions via fluorescence anisotropy - Tang, Qing; Wei, Yuan-Ping; Ma, Ruiqi; Wei, Na; Zhou, Tammy Zihan; Ho, Hilary Kung-Yu; Bhat, Zafar Iqbal; Ishrat, Iqra; Li, Xiaoyu; Yam, Judy Wai Ping; Wong, Yung Hou; Wang, Qiankun; et al. (浪淘沙预印本平台, 2026)
Proteolysis Targeting Chimera (PROTACs) are a revolutionary drug modality that can expand the repertoire of druggable targets to proteins lacking conventional active sites or binding pockets1. However, the majority of PROTACs developed are against already drugged targets2 suggesting it is challenging to discover novel binders of undruggable targets. To overcome this, we developed a scalable, efficient, and accessible method to detect cellular protein-small molecule interactions. Cellular Fluorescence Anisotropy (CFAST) measures cellular protein levels through changes in fluorescence anisotropy of a triangulenium dye-labeled nanobody probe. Centrifugation and nuclease incubation remove unwanted cellular components. We demonstrate that CFAST robustly detects cellular PARP1, MK2, and EGFP protein levels. Small molecule incubation, followed by heating and centrifugation, enables detection of cellular protein-small molecule interactions through thermal stabilization of the target protein. CFAST successfully detects cellular PARP1 and MK2 inhibitor binding in a dose-response manner. High-throughput CFAST screening identified a small molecule binder of undruggable transcription factor SOX2. This screening method also enabled development of a bifunctional PROTAC that simultaneously degrades membrane-bound oncogene EGFR and inhibits immune modulating target HRH1. CFAST takes a minimum of 2-3 hours to execute. It utilizes common lab equipment and reasonably priced reagents. Our work suggests that CFAST is a viable method to enhance drug and probe discovery through scalable, fast, and economical detection of cellular protein-small molecule interactions.